The relationship between non-government organisations and local government authorities in Tanzania: A case study of Morogoro and Babati district councils - Mpamila Madale Martin (Mzumbe University and Agder University College, 2026)
This is a study of the relationships between local government authorities and NGOs in Tanzania. But also of the more general nature of NGOs; their background and their contributions and limitations. For instance, there seems to be a certain measure of mistrust and suspicion between NGOs and LGAs, and sometimes there is a lack of co-ordination of the efforts of the NGOs in a district. The study has been conducted in the districts of Babati and Morogoro and the instrument used has been that of guided interviews. A main conclusion is that NGOs are not homogeneous, and that it is difficult to generalize. However, the NGOs normally are able to incorporate voluntarism in their organisational structure, and they have the advantage of relating to beneficiaries. Also it may be said that the NGOs have become more and more important as deliverers of services, partly as a response to the cut-backs in the service provision by the authorities. The NGOs mostly operate in close contact with the LGAs, but the flow of information and the co-ordination are not always satisfactory. One reason for this state of affairs is the lack of resources on the part of the LGAs, who are not able to follow up the NGOs properly